PENINGKATAN KINERJA KEUANGAN MELALUI PENGELOLAAN KEUANGAN, LITERASI KEUANGAN DAN INKLUSI KEUANGAN - Ni Luh Eka Ayu Permoni; Ni Kadek Oki Arsita Dewi Oki (ARTHA SATYA DHARMA, 2023)
Micro, Small and Medium Enterprises (MSMEs) are an important part of the economy because they are able to help restore the people's economy from the smallest scale. This research is research that aims to reveal ways to improve financial performance in MSMEs through financial management, financial literacy and financial inclusion in MSMEs. Data collection techniques in this study used literature review, documentation, interviews, and questionnaires. The type of data used in this study uses quantitative data. The sampling technique in this study used a purposive sampling technique. In this study, financial management variables have a positive and significant effect on financial performance, financial literacy variables have a positive and significant effect on financial performance and financial inclusion variables have a positive and significant effect on financial performance. From the results of this study it can be concluded that the financial performance of MSMEs can be improved through improvements in financial management, financial literacy and financial inclusion in MSMEs.